Albumin helps mediate removal of taurocholate by rat liver. - Forker, E L (1981)
Perfused rat liver removes 97% of the taurocholate from the afferent circulation when the perfusate albumin concentration is 0.5 g/dl. Increasing the albumin concentration 10-fold reduces the concentration of free taurocholate by a factor of five but produces only a 50% reduction in the apparent uptake coefficient. A similar discrepancy is evident from a model-independent analysis of the extraction fractions. From these observations we argue that uptake is not driven solely, or even predominantly, by the plasma concentration of free taurocholate but also depends on interaction between albumin and the cell surface. Nonequilibrium binding, saturation kinetics, and an inhomogeneous population of liver cells are considered as alternative explanations and excluded. The possibility that albumin exerts its effect by enhancing the diffusion of taurocholate across an unstirred layer in the Disse space appears improbable but cannot be eliminated.